Instagram Social Media @Adiba_Cake as a Promotional Medium for Product Sales - Salsabila Aurelia; Dianti Nur’aeni; Farida Nurfalah (Greenation Research & Yayasan Global Resarch National, 2025)
Social media has become an essential platform for disseminating information and interacting with the public. One of the most popular social media platforms is Instagram. The Instagram account @adiba_cake has utilized Instagram as a promotional medium to sell cake products. The purpose of this study is to explore the communication strategies used by @Adiba_cake in interacting with its followers, analyze their forms, and investigate how @Adiba_cake builds its brand identity. The research method employs a qualitative approach with data collection techniques including observation, interviews, and documentation. The research informants consist of the owner of the @adiba_cake account and active followers who engage with the content. The findings indicate that this account has successfully utilized social media as an effective promotional tool. This success is supported by active communication, clear product information, follower engagement, consistent visual identity, and interactions that strengthen relationship.